Pollutant emissions during the pyrolysis and combustion of starch/poly(vinyl alcohol) biodegradable films. (October 2020) - Moltó, J.; López-Sánchez, B.; Domene-López, D.; Moreno, A.I.; Font, R.; Montalbán, M.G.
Abstract: The massive use of petroleum-based polymers and their improper waste treatment has brought on significant global environmental problems due to their non-biodegradable nature. Starch/poly(vinyl alcohol) (PVA) bioplastics are suitable substitutes for conventional polymers, such as polyethylene, due to their full biodegradability and excellent mechanical properties. Knowledge of the pollutant emissions during pyrolysis and combustion of starch/PVA films is important because they can arrive at landfills mixed with conventional polymers and be thermally degraded in uncontrolled fires. On the other hand, controlled thermal treatments could result in thermal valorization of the waste. Pyrolysis and combustion experiments were carried out at 650, 750, 850 and 950 °C in a laboratory furnace. The analysis of carbon oxides, light hydrocarbons, and semivolatile compounds, including polycyclic aromatic hydrocarbons (PAHs), is shown. Experiments showed lower pollutant emissions than those found with conventional polymers, such as polyethylene and polyester, in the same equipment. Nevertheless, the pyrolysis run at 950 °C showed the highest light hydrocarbon yield (123013 mg kg −1 ), but this is considerably lower than the values found for polyethylene. The main semivolatile compounds (not PAHs) emitted, with maximum yields ranging from 1351 to 4694 mg kg −1, were benzaldehyde, phenol, indene, and acetophenone. Specifically, the total semivolatile compounds emitted after pyrolysis and combustion of starch/PVA samples represent only 38 and 50%, respectively, of those emitted with polyethylene. Further, the main PAHs were naphthalene, acenaphthylene, and phenanthrene with maximum values of 4694, 2704 and 1496 mg kg −1, respectively. The PAH yield was considerably higher in experiments with low oxygen content. Highlights: Pollutant emissions from thermal decomposition of starch/PVA films have been studied. The maximum formation of the 16 PAHs was found in the pyrolysis run at 950 °C. TEQ values increase with temperature and decrease when the oxygen content increases. Emissions of PAHs from starch/PVA films were considerably lower than with PE.